Legal Transformation of Trading Businesses into Individual Limited Companies for Indonesian Micro and Small Enterprises - Yani, Teuku Ahmad; Kurniawan, Andri; Mahfud, Mahfud; Hamdi, Syaibatul; Sautunnida, Lia (SCAD Independent, 2024)
This study discusses the transformation from a Trading Business (UD) to an Individual Limited Company (PT Perorangan) as an effort to empower micro and small enterprises in Indonesia. In the context of corporate law, this transformation provides a strong legal basis and good corporate governance, enabling a Trading Business to obtain legal entity status as well as broader access to funding sources and legal protection. Utilizing a normative legal research approach, this study analyzes related legislation and assesses its impact on the sustainability of micro and small enterprises. The findings indicate that this transformation not only enhances legal certainty but also offers opportunities for companies to grow more professionally and sustainably. Moreover, the obligation to report financial documents digitally increases transparency and trust among business partners. The findings of this study are expected to make a significant contribution to the literature on empowering small businesses and encourage the government to continue supporting the transformation of Trading Businesses into Individual Limited Companies as part of an inclusive economic development strategy.